STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KUALITAS LULUSAN DI MADRASAH IBTIDAIYAH NEGERI 2 KOTA MALANG - Fitri Lailatul Maghfiroh; Anwar Sa'dullah; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
The quality of education can be seen from the quality of graduates. This provides a challenge for the headmaster to improve the quality of graduates. With all available facilities, the school is expected to be able to prepare the right strategy in providing educational services to students. This study aims to find out how the principal's strategy in improving the quality of graduates in the state madrasah ibtidaiyah 2 Malang city which is on the road to Kemantren II No 26 so that many of its graduates continue in superior junior high schools. This study uses a qualitative approach where the data obtained is based on the results of observations, interviews, and documentation. The results of the study indicate that the head of the Islamic board designed the strategy and applied it to the activities of students so that these efforts could improve the quality of graduates.Keywords: Strategy, headmaster, quality of  graduates